Enhancing Nursing Students’ Knowledge in Emergency Stroke Care through Video-Based Learning - Indah Dwi Astuti (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2026)
Introduction: Stroke is an emergency condition that requires rapid and appropriate management. Nursing students’ understanding of stroke emergency care is essential to support clinical competence. However, evaluation results indicate that students’ comprehension is still limited. Video-based learning media is one of the innovations to improve learning effectiveness. The purpose this research was to examine the effect of video-based learning on improving students’ understanding of emergency nursing care in stroke. Methods: This study employed a pre-experimental one group pretest-posttest design. A total of 39 nursing students were recruited using total sampling. The instrument was a knowledge test, and data were analyzed using the Paired T test Signed Rank Test Results: The results this research showed that the mean pretest score was 82.72, which increased to 92.03 in the posttest. The Paired T test test showed a significant difference between pretest and posttest scores with p value = 0.000 (< 0.05). Conclusions: Video-based learning is effective in enhancing students’ understanding of stroke emergency nursing care. Video can be recommended as an innovative medium in nursing education to improve students’ learning outcomes